Genetic structure of milk proteins in Argentinian Holstein and Argentinian Creole cattle - Poli, M. A. (1991)
The genetic structure of milk proteins was studied in two completely different breeds: Argentinian Holstein (dairy breed; n = 377) and Argentinian Creole cattle (native breed; n = 161). Fairly large similarities were observed among Argentinian Holstein allelic frequencies reported in the present study and the values described in the literature for other Holstein populations. The high frequency of αs1-Cn gene was the most remarkable gene frequency difference between Holstein and Creole breeds. Gametic phase disequilibrium was found among three casein loci but not between casein and β-lactoglobulin loci. Both breeds showed the same gametic disequilibrium in β-Cn A/k-Cn A and β-Cn A/k-Cn B haplotypes; however, the αs1-Cn B/β-Cn A haplotype was only in disequilibrium in Holstein breed. In general, the gametic phase disequilibrium found in both breeds was similar to those described for other breeds. The possible causes of gametic disequilibrium are discussed, and the results suggest that natural selection could be the most likely explanation.